2009
DOI: 10.1007/s00586-009-1199-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intra-operative sternum vertical displacement on the sagittal curves of the spine

Abstract: Patient positioning is an important step in spinal surgeries. Many surgical frames allow for lumbar lordosis modulation due to lower limb displacement, however, they do not include a feature which can modulate thoracic kyphosis. A sternum vertical displacer (SVD) prototype has been developed which can increase a subject's thoracic kyphosis relative to the neutral prone position on a surgical frame. The kyphosis increase is obtained by lifting the subject's torso off the thoracic cushions with a dedicated stern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Finally, subsequent patient positioning on the surgical frame can also be used to increase sagittal curves such as by extending the lower limbs 15 or raising the sternum. 25 As with earlier studies, 3 all Cobb angles were reduced due to prone positioning; both MT and TL/L showed significant reductions on the MFPF and RH. TL/ L curves had higher reductions than MT curves 26% versus 15% on the MFPF and 38% versus 26% on the RH.…”
Section: Discussionsupporting
confidence: 54%
“…Finally, subsequent patient positioning on the surgical frame can also be used to increase sagittal curves such as by extending the lower limbs 15 or raising the sternum. 25 As with earlier studies, 3 all Cobb angles were reduced due to prone positioning; both MT and TL/L showed significant reductions on the MFPF and RH. TL/ L curves had higher reductions than MT curves 26% versus 15% on the MFPF and 38% versus 26% on the RH.…”
Section: Discussionsupporting
confidence: 54%
“…Although we did not directly measure lumbar lordosis in our study, it is thought that altered lumbar mobility might affect hip exion and extension values. Driscoll et al [34], for example, found that hip exion extension was associated with lumbar lordosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, most clinicians consider only the pelvic position [33]. Among the factors related to the spine, the sternum is related to thoracic kyphosis, and the inclination of the sacrum and pelvis is related to lumbar lordosis [35,36]. Kiebzak et al, (2022) observed fluctuations in the angle of the sternum and sacrum and reported that lifting the sternum is effective in postural correction [32].…”
Section: Introductionmentioning
confidence: 99%